Hubungan Asupan Lemak dan Serat dengan Kadar Kolesterol pada Penderita DM Tipe 2 - Wiardani, Ni Komang; Dewantari, Ni Made; Ima Purnami, Kadek; Prasanti, P.A.Gita (Jurusan Gizi, Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2018)
Regulation of fat and fiber intake plays an important role on blood cholesterol levels for patients with DM. Excessive intake of fats especially saturated fat with low fiber intake can increase cholesterol levels in people with type 2 diabetes that trigger the occurrence of cardiovascular complication disease. The aim of this study to know the correlation between fat and fiber intake with blood cholesterol level of DM type 2 patient. The study was an observational study with cross sectional design with subjects of outpatient type 2 diabetes mellitus RSUP Sanglah Denpasar amounted to 97 people. The data collected included total fat intake, saturated fat and fiber with 1 x 24 hour recall method and total cholesterol level using enzymatic method using multichek parameter. The results showed that 52.6% of the subjects were female and 47.4% male. The average total fat intake was 52.1 g / day, saturated fat 15.0 g / har, fiber 22, 5 g / gari and mean cholesterol levels 210.4 mg / dl. Fat intake found in subjects exceeded the recommended requirement of total fat 77.4% and saturated fat 55.7%, while fiber intake 55.7% less than recommended. A total of 56.7% subjects had high cholesterol levels (> 200 mg / dl). There was a significant relationship between fat and fiber intake with cholesterol levels in the subjects (p <0.05, ÃÂ± = 0.05)Keywords: fat intake, fiber, cholesterol level, type 2 DM